2020
DOI: 10.3389/fneur.2020.00192
|View full text |Cite
|
Sign up to set email alerts
|

Rare Disease: Cardiac Risk Assessment With MRI in Patients With Myotonic Dystrophy Type 1

Abstract: Introduction: To evaluate myocardial strain and extracellular volume in myotonic dystrophy type 1 (DM1) patients as potential imaging biomarkers of subclinical cardiac pathology. Materials and methods:We retrospectively analyzed 9 DM1 patients without apparent cardiac disease who had undergone cardiac magnetic resonance at our center. Patients were age-and sex-matched with healthy controls. The Mann-Whitney U test was used to compare cardiac strain between the two groups. The t-test was used to compare the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Luetkens et al studied a cohort of DM1 patients without known cardiovascular disease and found CMR evidence of diffuse fibrosis (i.e., increased T1 and ECV values; patchy and extensive increased LGE uptake) in about 35–40% of patients, decreased LV-ejection fraction, and decreased myocardial strain measurements [ 91 ]. Similar findings of increased ECV and decreased cardiac strain were reported in a smaller cohort of DM1 patients without evidence of cardiac disease [ 87 ].…”
Section: Imaging Studies and The Dm1 Heartsupporting
confidence: 86%
See 1 more Smart Citation
“…Luetkens et al studied a cohort of DM1 patients without known cardiovascular disease and found CMR evidence of diffuse fibrosis (i.e., increased T1 and ECV values; patchy and extensive increased LGE uptake) in about 35–40% of patients, decreased LV-ejection fraction, and decreased myocardial strain measurements [ 91 ]. Similar findings of increased ECV and decreased cardiac strain were reported in a smaller cohort of DM1 patients without evidence of cardiac disease [ 87 ].…”
Section: Imaging Studies and The Dm1 Heartsupporting
confidence: 86%
“…The last decade has seen multiple studies documenting cardiac magnetic resonance imaging (CMR) changes in the heart of individuals with DM1. Many investigators commented on the frequency of cardiac fibrosis and the possibility that CMR could be a valuable biomarker for DM1 [ 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. CMR can be used to assess the structural and functional parameters seen by echocardiography, and in addition, it provides a means for assessing fatty infiltration, edema and diffuse and focal fibrosis.…”
Section: Imaging Studies and The Dm1 Heartmentioning
confidence: 99%
“… 17 , 23 , 24 Several studies have examined the role of myocardial strain in patients with MD. 25 , 26 , 27 , 28 , 29 Of particular relevance, a recent study also applied a 3D strain analysis technique to study conventional, geometry‐dependent measures in 111 patients with a broad range of neuromuscular diseases inclusive of, but not limited, to MD. 29 Similar to our study, they observed both 3D‐GCS and 3D‐GRS are associated with the presence of replacement fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Mid-wall late gadolinium enhancement (LGE) has been reported, most often in the septal/ inferolateral segments, 16,18,[26][27][28][29][30][31] and an enlarged extracellular volume has been demonstrated through mapping techniques. 16,17,28,30,32 The link between CMR findings and electrical disturbances in DM1 is controversial [16][17][18][27][28][29][30][31][32][33][34] and their prognostic significance is unclear.…”
Section: Introductionmentioning
confidence: 99%